Socioeconomic impact assessments of high-Speed rail: A meta-Analysis. Issue 4 (4th July 2022) - Cheng, Junmei; Chen, Zhenhua
ABSTRACT: The interest in the socioeconomic impact assessments of the high-speed rail (HSR) system is burgeoning as many countries are considering investing in such a system. While extensive studies have provided a wide range of evaluations of HSR on the socioeconomic impact, primarily from an ex-post perspective, it remains unclear how reliable the evaluation outcomes were, given the variety of data, method and research framework being adopted. This paper provides a comprehensive review of the socioeconomic impact studies of high-speed rail (HSR), based on 242 academic publications. In particular, we examined to what extent the impact outcome is influenced by various modelling factors, such as data, model, and research design, using meta-analysis based on 368 empirical estimates derived from 45 empirical studies. Our analysis confirms that the factors of research design (e.g. variables, data, and modelling method) do have various influences on the empirical estimates of HSR project appraisals. In the end, the paper discusses the implications for future infrastructure project appraisals.